Case management in early psychosis intervention programme: perspectives of case managers. Issue 2 (3rd April 2019) - Wong, Horng Hien; Shahwan, Shazana; Verma, Swapna; Subramaniam, Mythily
ABSTRACT: Aim : This qualitative study elicited the perspectives of case managers (CM) on case management, with the aim to understand salient aspects of case management from their own perspective. Methods : This study was conducted as part of a larger study that explored the perspectives of clients, caregivers and case managers on case management. All CMs except the CM researchers were recruited. Two CM focus group discussions (FGD) were conducted and facilitated by an experienced independent researcher from the research department. The FGDs were audio recorded and transcribed verbatim with all participants' identifiers omitted to protect confidentiality. Qualitative thematic analysis was conducted using NVivo V.10. (QSR International. NVivo V.10 (Computer software). 2012.http://www.qsrinternational.com ) Results : Eleven themes emerged from the CM FGDs which are based on the CMs' work with both clients and caregivers: therapeutic alliance, holistic monitoring, collaborative role with other care providers, counselling and guidance, crisis management, bridging role, client-centred care, client empowerment and strength building, psychoeducation, support and advocacy. Conclusions : The voices of CMs are important in planning service delivery models and improving the quality of care to clients and caregivers.